Translation, adaptation and validation of the American short form Patient Activation Measure (PAM13) in a Danish version - Sokolowski Ineta; Maindal Helle; Vedsted Peter (BMC, 2009)
Abstract Background The Patient Activation Measure (PAM) is a measure that assesses patient knowledge, skill, and confidence for self-management. This study validates the Danish translation of the 13-item Patient Activation Measure (PAM13) in a Danish population with dysglycaemia. Methods 358 people with screen-detected dysglycaemia participating in a primary care health education study responded to PAM13. The PAM13 was translated into Danish by a standardised forward-backward translation. Data quality was assessed by mean, median, item response, missing values, floor and ceiling effects, internal consistency (Cronbach's alpha and average inter-item correlation) and item-rest correlations. Scale properties were assessed by Rasch Rating Scale models. Results The item response was high with a small number of missing values (0.8-4.2%). Floor effect was small (range 0.6-3.6%), but the ceiling effect was above 15% for all items (range 18.6-62.7%). The α-coefficient was 0.89 and the average inter-item correlation 0.38. The Danish version formed a unidimensional, probabilistic Guttman-like scale explaining 43.2% of the variance. We did however, find a different item sequence compared to the original scale. Conclusion A Danish version of PAM13 with acceptable validity and reliability is now available. Further development should focus on single items, response categories in relation to ceiling effects and further validation of reproducibility and responsiveness.